Frequency domain estimation method of the characteristic period of the P wave of earthquakes - Donciu, Codrin; Serea, Elena; Temneanu, Marinel Costel (Frontiers in Physics, 2025)
Early warning system earthquake alerts exploit the time delay that the surface waves have in reference to the P waves and estimate the magnitude based on the interpretation of the specific parameters of the P waves. One of the most commonly used parameters for estimating the moment magnitude of an earthquake is the characteristic period measured in the first 3 s after the appearance of the P wave. The classic method determines the characteristic period in the time domain by using the velocity and displacement waves of the acquired samples. In this paper, we present a new method for estimating the characteristic period through its corresponding frequency. This method includes zero padding of the P-wave sequence, conversion of the extended sequence from the time domain to the frequency domain, identification of local frequency maxima, and calculation of the weighted average of the frequency based on the identified maxima. Tests conducted on synthetic signals, as well as standard deviation evaluation tests for simultaneous recordings at several seismic stations, revealed better performance than the classic method in terms of noise immunity and number of false alarms.